Current Knowledge of Mycobacterium Other Than Tuberculosis (MOTT) in this Current Era: Definition, Taxonomy, and Diagnose - Indriani, Sri Indah; Pratiwi, Adelia; Simatupang, Elvando Tunggul Mauliate; Simanjuntak, Arya Marganda (Indonesian Society of Respirology (ISR), 2024)
Globally, Pulmonary Tuberculosis (PTB) remains a health concern, with an annual increase in cases. Indonesia is the second-highest contributor to PTB cases globally, below India, which also saw an increase in cases, particularly after the COVID-19 pandemic. Nontuberculous Mycobacteria (NTM) infections contribute to the increase in PTB cases through misdiagnosis and overlapping conditions. The occurrence of changes in the composition of NTM species in the Mycobacterium genus is the premise for updating the diagnosis of NTM with several supporting examination modalities. Clinical, radiological, and microbiological criteria have been established by the American Thoracic Society (ATS) and Infectious Diseases Society of America (IDSA) for the diagnosis of NTM. The relationship between these three criteria is essential as a guideline for distinguishing infections caused by Mycobacterium tuberculosis (Mtb) from those caused by NTM.